Personal pronouns in Lithuanian scientific discourse - Linkevičienė, Nijolė; Šinkūnienė, Jolanta (Kalbotyra, 2012)
The focus of the paper is the use of personal pronouns as a means of author stance expression in the Corpus Academicum Lithuanicum (about 9 million words) representing a variety of academic genres in five science areas (Biomedical sciences, Humanities, Physical sciences, Social sciences, Technological sciences). Pronouns in the subject position in Lithuanian may be omitted, as the person/number inflection of the verb already indicates the subject. Therefore, when the pronoun does occur in scientific discourse it might be interpreted as an emphasized expression of the author stance.In this study qualitative and quantitative approaches are employed to reveal distributional information and usage patterns of the personal pronouns I and we. The results of the study indicate cross-disciplinary differences in the use of personal pronouns in different science areas: researchers in the hard science fields tend to use personal pronouns to a much smaller extent than researchers in the soft fields. The study also showed marked differences in the distribution of exclusive and inclusive we. Scientists in the humanities and social sciences prefer the inclusive communal we, whereas researchers in biomedical, physical and technological sciences favour the exclusive we which primarily refers to the authors themselves or to the academic community. A case study of the personal pronoun yourevealed its rare usage in scientific Lithuanian. This pronoun is usually employed to refer to the indefinite addressee.
Keywords: academic discourse; author stance; personal pronouns; inclusive we; exclusive we